2008
DOI: 10.1016/j.bbmt.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymorphism within the Heme Oxygenase-I Promoter on Overall Survival and Transplantation-Related Mortality after Allogeneic Stem Cell Transplantation

Abstract: Aside from major and minor histocompatibility antigens, genetic polymorphisms of various donor and host genes have been found to be risk factors for graft-versus-host disease and transplantation-related mortality (TRM). The heme oxygenase I (HO-I) protein has been implicated in regulating inflammatory response and has been described as a "protective gene" in solid organ transplantation. In humans, the promoter region displays length polymorphism due to a variable number of GT repeats. Individuals exhibiting 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…In a cohort of 92 patients transplanted with in vivo T-cell depleted grafts from matched related donors MA-HCT, Gerbitz et al observed that donors with high HO-1 expression (based on (GT) n repeat genotype) and thus increased anti-inflammatory drive, were associated with inferior survival due to grade III-IV acute GVHD≥3 [15]. Gerbitz et al hypothesize that expression of HO-1 above a certain threshold may lead to an excessive oxidative burst that induces tissue damage [16].…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort of 92 patients transplanted with in vivo T-cell depleted grafts from matched related donors MA-HCT, Gerbitz et al observed that donors with high HO-1 expression (based on (GT) n repeat genotype) and thus increased anti-inflammatory drive, were associated with inferior survival due to grade III-IV acute GVHD≥3 [15]. Gerbitz et al hypothesize that expression of HO-1 above a certain threshold may lead to an excessive oxidative burst that induces tissue damage [16].…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in genes encoding for nucleotide-binding oligomerization domain 2 (NOD2)/caspase recruitment domain 15 (CARD15), 9 heme oxygenase-1 (HO-1) promoter, 6 nase citullinating enzymes 4 (PADI4) 13 and methylenetetrahydrofolate reductase (MTHFR) 14 have been shown to influence the outcome after allogeneic SCT. Most of them are associated with the development of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous investigations have revealed that several single nucleotide polymorphisms (SNP) which affect individual immune response to infections and inflammatory reactions are associated with the risk of GVHD and transplant outcomes. [4][5][6][7][8][9][10][11][12][13][14][15] NKG2D is an activating and co-stimulatory receptor belonging to the C-type lectin-like family of transmembrane proteins and is expressed as a homodimer on natural killer (NK) cells, CD8…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous investigations have revealed that several single-nucleotide polymorphisms (SNPs), which impact on individual immune response to infections and inflammatory reactions are associated with SCT outcomes including the risk of acute GVHD. [3][4][5][6][7][8][9][10][11][12] IL-17, also known as IL-17A, is the hallmark cytokine of a new T-helper subset termed Th17. [13][14][15][16] gdT cells, macrophages and neutrophils are sources of IL-17 as well.…”
Section: Introductionmentioning
confidence: 99%